Parental Self-Perception, Parental Investment, and Early Childhood Developmental Outcomes: Evidence From Rural China - Wang, Lei; Wang, Ting; Li, Hui; Guo, Kaiwen; Hu, Lynn; Zhang, Siqi; Rozelle, Scott (Frontiers in Public Health, 2022)
Using a three-wave longitudinal survey conducted in 815 households in rural Western China, this study aims to examine the association between parental self-perception and early childhood development and the mediation effect of parental investment on the association between parental self-perception and child development when the sample children are at different ages in the early childhood (18–30, 22–36, and 49–65 months). The results demonstrate that parental self-perception are positively and significantly associated with child social-emotional development in all three ages of childhood (from 18 to 65 months). Positive and significant association between parental self-perception and child cognitive development is found in the ages from 22 to 65 months. In addition, findings of this study show that parental investment plays a mediating role in the association between parental self-perception and child cognitive development. The study calls on policymakers to help to strengthen parental self-perception and parental investment related to early childhood development, which should result in better child development in rural China.